Ni0.48Cu0.12Zn0.40Gd0.04Fe1.96O4 (Ferrite) sample preparation, planetary ball milling and calcination - Noor, Lamisha (BRAC University, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Applied Physics and Electronics, 2017.